Analisis Faktor-Faktor yang Berpengaruh pada Belanja Bidang Pelaksanaan Pembangunan Desa - Pratama, I Gede Aditya Adhe; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p12, 2021)
This study aims to examine the effect of Village Original Income, Village Funds, Regional Tax and Levy Revenue Sharing, Village Fund Allocation, and Special Financial Assistance on Expenditures for the Implementation of Village Development. This research data was collected using the saturated sample method, the entire population which includes the financial statements of 133 villages in Tabanan Regency from 2017 to 2019 was used as a research sample, so the research sample amounted to 399. The data collection method was carried out by the documentation method, with the analytical technique used was the Multiple Linear Analysis. The results of this study stated that village funds, regional tax and levy revenue sharing, and special financial assistance had an effect on expenditures for the implementation of village development, while village original income and allocation of village funds had no effect on expenditures for the implementation of village development. Keywords: Village Original Income; Village Fund; Regional Tax and Retribution Sharing; Village Fund Allocation; Special Financial Assistance.